Requirements Gathering for Specialized Information Systems in Public Administration - Šimonová, Stanislava (IEEE (Institute of Electrical and Electronics Engineers), 2021)
Identification of quality requirements is a necessary prerequisite for the development of a functional information system, collection, and analysis of data requirements and data functionalities are the initial steps in the general process of information system development. The quality of the process of collecting and evaluating requirements is a fundamental prerequisite for the created information system to accurately support the work needs of users. Users are therefore interested in participating in this requirements collection process. However, the situation is different for information systems in public administration, the aim of which is regulation and restriction. Here, the reluctance of users to cooperate and pass on the information needed for further development of the system can be assumed. This can then be reflected in the malfunction of the information system in the sense of incorrect support in the enforcement of regulation or restriction by the public administration. The article deals with the process of collecting and evaluating requirements for the restriction targeted information systems.
Shromažďování požadavků pro specializované informační systémy ve veřejné správě
Keywords: information system; voice of user; requirements gathering; support tools